2015
DOI: 10.1007/s00464-015-4455-8
|View full text |Cite
|
Sign up to set email alerts
|

30-Day readmission after bariatric surgery in a publicly funded regionalized center of excellence system

Abstract: The readmission rate after bariatric surgery in Ontario is similar to other major population-based bariatric surgery programs. Complications on initial admission and prolonged length of stay were independent predictors of readmission. Considering a large proportion of the readmissions were short term, future research into potential measures to prevent these readmissions is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
(87 reference statements)
1
19
1
3
Order By: Relevance
“…In another, patients who underwent LRYGB had 60% higher risk for readmission in the 30-day postoperative time period compared to those who underwent LSG [ 34 ]. Contrary to this, we and Doumouras et al did not observe similar relationship [ 26 ]. Operative time and intraoperative adverse events were also proved to increase risk of readmission [ 34 , 47 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In another, patients who underwent LRYGB had 60% higher risk for readmission in the 30-day postoperative time period compared to those who underwent LSG [ 34 ]. Contrary to this, we and Doumouras et al did not observe similar relationship [ 26 ]. Operative time and intraoperative adverse events were also proved to increase risk of readmission [ 34 , 47 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Recent study by Sippey et al reported an overall 30-day readmission rate after LSG or LRYGB of 5.1% [ 25 ]. Other authors reported readmission rates after those two procedures in the range of 1.87–14.16% [ 18 , 26 33 ]. Despite many authors reporting more common readmissions after LRYGB compared with LSG [ 25 , 27 , 28 , 34 ], one study documented higher rates after LSG [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative bleeding that requires intervention occurs in up to 11% of cases in both the RYGB and SG. 23 Fortunately, 85% of patients are likely to stop without surgical intervention. 24 Patients with dysmetabolic syndrome X have a higher risk for bleeding.…”
Section: Early Complicationsmentioning
confidence: 99%
“…Telem et al [34] reported that 17.5% of patients who underwent primary bariatric surgery had unplanned ED appearances. Doumouras et al [35] reported a readmission rate of 6.1% over a period of 3 years. Saunders et al [36] reported 1-year readmission rate of 18.8%.…”
Section: Introductionmentioning
confidence: 99%
“…According to international studies, several predictors for hospital readmission or ED visits after bariatric surgery were identified. The most important predictors for readmission were found to be age, sex, BMI, diabetes, steroid use, hypertension, type of procedure, and operative time [28,35,37]. In addition, the surgical procedure type has been associated with postoperative ED visits [31].…”
Section: Introductionmentioning
confidence: 99%